Alfers, Pool, And Mugleston, Eds., Perspective On America, Volume 2 - Reading In United States History From 1822 - Wantland, William (Teaching History: A Journal of Methods, 1999)
In Readings in United States History editors Kenneth G. Alfers, C. Larry Pool, and William Mugleston have compiled articles that include some very well-known events and people in American history, such as George Armstrong Custer and the Battle of the Little Big Hom, steel magnate Andrew Carnegie and his influence on American society and the Industrial Revolution, the Populist Movement of the 1890s, the causes and con;;equences of the Stock Market Crash of 1929, the "man of the century"-Franklin D. Roosevelt, the controversial Lydon B. Johnson, and finally the equally frustrating war conducted by LBJ-the Vietnam War.